Pengendalian mutu pendidikan anak usia dini melalui pembinaan kinerja pendidik dengan cara on the job and off the job training di korwil dindikpora - Rokhadi Rokhadi (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
Early childhood education is the most strategic stage of education in efforts toincrease human resources. However, it will be successful if it is supported by the quality of implementation, especially the performance of the educators. Therefore there needs to be quality control efforts through fostering teacher performance by means of on the job and of the job training. Based on theoretical exposure and discussion of problems, it can be concluded as follows: (1) That early childhood education has a strategic role in preparing resources quality human resources in the future; (2) The administration and implementation of early childhood education, especially in the informal route, has not shown the expected quality, both in facilities and infrastructure and in the performance of educators; (3) PAUD supervisors have a strategic role in coaching educators at both the institutional, village and sub-district levels through On the job Training and Off the job Training approaches to improve Educator competencies which include pedagogical, professional, social and personality; (4) PAUD supervisors need or must equip themselves with the various abilities needed in the implementation of the Educator competency development function.